Phytochemicals as weapons against drug resistance - Kruttika, Jan; Karthick Kumar, Alagamuthu; Joseph, Kadanthottu Sebastian; Kuppusamy Alagesan, Paari; Aditi, Chaudhary; Manikantan, Pappuswamy; Keerthi , G Rao; Stena Jesima, Rebello; Medini, Deshpande K (Plant Science Today, 2023)
Phytochemicals are plant-based products with high medicinal value. These metabolites effectively target disease-causing microbes. Drug-resistant pathogens have developed mechanisms to sustain themselves even with inhibitors. Drug resistance has emerged as a global giant, causing all available treatment options to fail. The solution to this problem is in the phytochemicals of plants with antibacterial and drug resistance modulation properties. Phytochemicals might be able to get rid of efflux pumps, drug-modulating enzymes, resistance genes, quorum sensing, and biofilm, all of which cause pathogens to be resistant to drugs. Moreover, anti-obesogenic and cardioprotective properties are also observed in phytochemicals. Additionally, studies show the success of phytochemical-based nanoparticles in drug resistance regulation. This review emphasizes phytochemicals' different mechanisms of action and their derivatives in curbing drug-resistant pathogens and cancer cells.